New South Australian colony. (1836)
Detailed description of the first emigrants bound for Port Lincoln. The dinner guest list included Torrens, Wakefield, Bulwer, Ward, Attwood and Capt. Berkeley. The dinner was on board the Coromandel.
Also available online
Keywords: Coromandel (Ship); Immigrants -- South Australia; Curiosities and wonders -- Australia; South Australia -- Colonization; South Australia -- Emigration and immigration